A Pragmatic Analysis of Politeness Strategies of Directive Expression Reflected in ‘Inglorious Basterds’ Movie - Hafiz Alfandi Rizqy; Havid Ardi (English Language and Literature, 2020)
This research studies about politeness strategies and translation technique in Inglorious Basterds movie and its Indonesian translation. The purposes of the research are to know the kinds of politeness strategies which is used by the main characters in directive utterance and how does the translator translate the politeness strategies of directive act into subtitle. The data of this research are Inglorious Basterds movie and its Indonesian translation. This research is done by descriptive qualitative method, and focus on a single case. The research findings show that there were 4 types of politeness strategies and 12 translation techniques in 168 data. Based on the frequencies, the strategies applied in the data are Bald on Record 86 times (43%), Positive Politeness 57 times (29%), Negative Politeness 33 times (17%), and Off Record 22 times (11%).